Parametric optimization of passive envelope design under 2020 and 2050 climate conditions: A case study of Marrakech - KASMI, Houcine; MOUHAT, Ouadia (Edelweiss Applied Science and Technology, 2026)
This study evaluates the thermal performance of passive building envelope strategies under current (2020) and future (2050 under Representative Concentration Pathway 8.5) climate conditions in Marrakech, a hot semi-arid city facing increasing cooling demand. Glazing types, including tinted glazing (AL-Tinted) and low-emissivity glazing (Low-E), are used in building envelopes, along with phase change materials (PCM). A dynamic simulation approach was employed to assess 27 configurations combining different levels of expanded polystyrene (EPS) insulation, glazing types including tinted glazing (AL-Tinted) and low-emissivity glazing (Low-E) used in building envelopes, and phase change materials (PCM). Results indicate that in 2020, the most insulated configuration (EPS 10 cm + Low-E glazing + 4 cm PCM) reduced cooling demand by 62.7% but increased heating demand by 76.9%. Under future climate conditions, a configuration with moderate insulation (EPS 4 cm), Low-E glazing, and 4 cm PCM achieved the highest cooling reduction (−65.8%) while avoiding overheating. Configurations without insulation led to significant heating penalties exceeding +100%. The influence of envelope parameters shifts under climate change, with insulation dominating current performance and PCM becoming more significant in future scenarios. The findings highlight the need for climate-responsive design strategies, supporting a transition from insulation-driven approaches to adaptive combinations of glazing and thermal storage for hot climates.